Laser cladding of tool steel for grain boundary stability - Fazliana, Fauzun (2021)
Laser cladding is one of the best methods to modify the steel surface for enhanced thermal stability properties. Added carbide particle impeded the grain boundary migration which often occurred in metastable modified microstructure at high working temperature. In this thesis, an experimental study of laser cladding on H 13 tool steel with tungsten carbide (WC) particles addition is presented. The aim is to produce WC cladded layer with enhanced properties for high temperature applications specifically in die-casting. The laser cladding was conducted using laser systems of 1.06 µm wavelength. The preliminary experiment (DOE 1) was processed using the Nd:YAG laser while other DOE (DOE 2, DOE 3 and DOE 4) with fibre laser. The cladded layer of WC particles with sodium silicate and 4% PYA binder's agent was preplaced prior to laser processing. DOE I consists of 16 samples investigates the powder distribution on cladded layer at different parameter settings. Meanwhile, DOE 2 and DOE 3 investigate the effect of binders to powder distribution ratio on clad layer thickness as well as laser energy absorption of the surface. DOE 4 was developed using Box-Behnken design to study the powder distribution and grain evolution of cladded layer. All samples were characterised for hardness properties, depth of cladded layer, elemental changes in microstructure by EDXS analysis and phase transformation by XRD analysis. Thermal wear test that simulated die-casting environment was conducted to investigate the thermal stability of cladded layer. The thermal wear test involves cyclic heating ofcladded samples in molten aluminium alloy at an elevated temperature range of 800-850 °C and quenching in room temperature water bath, for I000, 3000 and 5000 cycles. Sample characterisation was carried out to measure the properties of thermally worn cladded layer. A thermal simulation was developed using ABAQUS software to study the distribution of thermal stress and temperature within cladded layer. The statistical analysis was conducted for DOE 4 with design optimisation. From the findings, powder distribution within clad layer improvement was achieved in samples of DOE 4. The resulted WC particle distribution in DOE 4 shows significant microhardness increment up to 70 %, due to high hardness carbides within the iron matrix. The EDXS analysis indicates WC particle dissolution in the clad layer where W element diffused to the grain boundary, thus strengthen the iron matrix. Four main phases were detected from XRD analysis namely; a-Fe, y-Fe, tungsten (W), tungsten carbide (W2C) and qusongite (WC). From the thermal wear test, mass loss and volume of the eroded surface of cladded samples shows an increment with an increasing number of thermal wear cycles. Crack formation and propagation were observed on the thermally worn cladded samples with the increasing number of thermal wear cycles. Phases like NiFeA104, CoW04 and FeW04 were diffracted on the thermally worn sample surface in addition to the existing phases (a-Fe, y-Fe and W2C) indicating oxidation and atomic diffusion occurred on the surface affected by thermal cyclic. Overall, laser clad samples hardness properties reduction was 23 %. Thermal modelling shows significant effect ofthermal fatigue parameter towards temperature and stress distribution on cladded sample. The statistical analysis generated optimised design at 0.901. These findings are significant to enhance surface properties especially thermal stability at high working temperature for dies and high wear resistant applications.